Embedded System Real Time Data Acquisition System Using FPGA Technology for Detection and Counting of PD Signal from PICO Pulse Generator - Emilliano; Chakrabarty C.K.; Basri A.; Ramasamy A.K.; Suhendi N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Cables; Controllers; Data acquisition; Field programmable gate arrays (FPGA); Microcontrollers; Partial discharges; Photonic integration technology; Signal detection; Signal sampling; Underground cables; Direct measurement; Fpga(field programmable gate array); High speed data acquisition system; Partial discharge signal; PIC microcontrollers; Processing capability; Real-time data acquisition systems; Sampling frequencies; Pulse generators